BOOK REVIEW: ENGLISH CURRICULUM AND MATERIAL DEVELOPMENT - Astri, Zul (LLT Journal: A Journal on Language and Language Teaching, 2022)
This textbook, entitled "English Curriculum and Material Development," covers a variety of subjects in 11 Chapters. It is good for educational practitioners who are always in touch with the curriculum and syllabus. This book was written by a lecturer at the Ponorogo State Islamic Institute named Pryla Rochmawati. It consists of 4 main parts, namely Curriculum and Syllabus, Component of Curriculum, Curriculum in Indonesian Context, and Material Development. However, here I will briefly explain one by one the chapters contained in this book.  Chapter 1 discusses the concept of curriculum and syllabus, including its definitions, the difference, kinds of the syllabus, and its importance in language teaching. Chapter 2 examines a component of the curriculum called Need Analysis. It discusses the definition, purpose, and targets, as well as the steps and techniques for doing a need analysis. Chapter 3 is concerned with the conceptualization of aims, goals, and objectives. Chapter 4 discusses Assessment and Testing, emphasizing the how and why of assessment and testing. Chapter 5 covers materials as a component of the curriculum. This section discusses the basis for material design, the material blueprint, and the origins of materials. Chapter 6 focuses on the teaching concept, which encompasses the roles of institutions, teachers, the teaching and learning process, and the application of curriculum through lesson plans. Chapter 7 examined the concept of evaluation. It discusses the approaches, purpose, and procedures used in conducting curriculum evaluation. Chapter 8 discusses the curriculum and syllabus in the Indonesian context. Chapter 9 discusses the SMA/MA English curriculum, including the syllabus and lesson plans for this grade. Chapter 10 focuses on the SMP/MTs level curriculum, including the syllabus and lesson plans for this grade. Finally, Chapter 11 examines the concept of material development in English language teaching. This textbook is intended to augment the teaching and learning processes in the English Curriculum and Material Development course, as well as to encourage students to be active and motivated learners.